KINERJA GURU PAUD DITINJAU DARI KUALIFIKASI PENDIDIK, PENGALAMAN MENGAJAR, DAN PELATIHAN - Julita Andriana; sumarsih sumarsih; delrefi d (Universitas Bengkulu, 2018)
This study to almed to describe Early Childhood Education teachers’ performance observed from teachers’ qualification teaching experience and trainning.The method of the study is quantitative descriptive method. The population of this research is all Early Childhood Education teachers’ who are teachig Early Childhood Education Kembang Sepatu group. The writer use total sampling consists of 30 teachers, 6 teachers are SI Early Childhood Education teachers’, 14 teachers are not from Early Childhood Education major teachers’, and 10 teachers are from Senior High School Graduated teacher. The technique for collicting the data is used questionnaire. The analysis data use percentage. The result of the study show that Early Childhood Education teachers’ performance observed from teachers’ qualification teaching experience and trainning are in this good category, with the percentage 75,9%. With details of teacher performance seen from the qualifications of teachers are SI Early Childhood Education teachers’ is in the category Very Good with a value of 83.3%, For teachers are not from Early Childhood Education major teachers’ is in the Good category with a value of 74.4% and teachers are from Senior High School Graduated teacher are in the Good category with 70% value. The performance of teachers whose teaching experience is more than 10 years is better than teachers whose teaching experience is under 10 years. The performance of teachers who have attended the training is better than the teachers who have never attended the training. For later study, the writer suggested that the reseaarcher to examine more in depth about the guiding and training aspects of the child.Keyword: Early childhood teacher’ performance observased by educator qualification from graduated senior high school